1995
DOI: 10.1042/bst0230112
|View full text |Cite
|
Sign up to set email alerts
|

Four ways of being an agonist: multiple sequence determinants of efficacy at D2 dopamine receptors

Abstract: A model describing the binding of catecholamines to receptors has been developed largely on the basis of in nitro mutagenesis of the B,-adrenergic receptor. According to this model, three points of interaction contribute much of the binding energy of catecholamines. A conserved aspartic acid residue in the third transmembrane domain, Asp-1 13 of the B,-adrenergic receptor, participates in an ionic interaction with the charged amine of agonists and antagonists, whereas two of three conserved serine residues clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…D2R also contains TM5 serine residues ( Supplementary Fig. 1a ), where mutagenesis studies support that they both contribute to ligand efficacy and overall G protein activation 32 , 33 , and are also essential for aripiprazole recognition 34 .…”
Section: Resultsmentioning
confidence: 98%
“…D2R also contains TM5 serine residues ( Supplementary Fig. 1a ), where mutagenesis studies support that they both contribute to ligand efficacy and overall G protein activation 32 , 33 , and are also essential for aripiprazole recognition 34 .…”
Section: Resultsmentioning
confidence: 98%
“…of the receptor's respective putative extracellular loops, especially e 2 and e 3 , and sometime their N-terminal segments. Similarly, wavelet transformation of the hydrophobically transformed amino acid series of the long form, D 2 dopamine receptor suggested leading eigenvector hydrophobic mode locations in the e 2 and e 3 regions (Mandell et al, 2003), extracellular to the transmembrane regions of the putative dopamine binding site (Dal Toso et al, 1989;Kozell et al, 1994;Neve and Wiens, 1995;Woodward et al, 1994). Mode-targeted, eigenvector template-designed peptides demonstrated significant positive modulatory effects on D 2 dopamine receptor-transfected cellular function, as well as dramatically augmenting dopamine-mediated behavior in the rat brain (Mandell et al, 2003).…”
Section: Locating Putative Allosteric Sites By Representing the M 1 Achr's Leading Eigenvector Modes As Modular Densities In The Morlet Wmentioning
confidence: 95%
“…Dopamine receptor mutation data. , Data is shown for the consensus binding pocket defined using structure-based generic position numbers from GPCRdb . Wild-type residues for the orthologues involved in mutation studies and the mutant residue are shown (note that only the mutations which have a data point shown in the table were actually carried out, the table is organized for comparability among orthologues).…”
Section: Dopamine Receptor Mutationsmentioning
confidence: 99%